2009
DOI: 10.1017/s1368980009005540
|View full text |Cite
|
Sign up to set email alerts
|

Household food insecurity is a risk factor for iron-deficiency anaemia in a multi-ethnic, low-income sample of infants and toddlers

Abstract: The prevalence of IDA in early childhood is significantly larger in low-income infants and toddlers living in VLFS households. Asian, Hispanic and African-American children have elevated prevalences of ID and IDA. Breast-feeding may be associated with elevated ID and IDA, while participation in the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) may be protective for ID.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
59
1
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 35 publications
6
59
1
6
Order By: Relevance
“…Additionally, in a convenience sample of MexicanAmerican children ages 3-6, children in food insecure families were less likely to meet USDA Food Guide Pyramid guidelines [1]. In at least two other studies of infants and toddlers, food insecurity has been shown to be associated with iron deficiency anemia [25,26]. These consistent and significant associations between food insecurity and indicators of diet quality across participants and settings of the studies described previously suggest that food and drink intake is a critical pathway linking food insecurity and poor health and is a potential avenue for intervention.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, in a convenience sample of MexicanAmerican children ages 3-6, children in food insecure families were less likely to meet USDA Food Guide Pyramid guidelines [1]. In at least two other studies of infants and toddlers, food insecurity has been shown to be associated with iron deficiency anemia [25,26]. These consistent and significant associations between food insecurity and indicators of diet quality across participants and settings of the studies described previously suggest that food and drink intake is a critical pathway linking food insecurity and poor health and is a potential avenue for intervention.…”
Section: Discussionmentioning
confidence: 97%
“…As described, the occurrence of food insecurity among families with young children has particularly serious developmental consequences for children. [14][15][16][17][18][19][20][23][24][25] Additionally, exposure to parental IPV is a risk factor for children's poor physical, emotional, behavioral, social, and cognitive functioning. 43,44 It is also a concern that the different sources of stress that children experience residing in violent households could lead to the intergenerational cycle of violence and food insecurity.…”
Section: Present Studymentioning
confidence: 99%
“…As consequências de se viver assim são inúmeras. Para a saúde da criança estão associados à anemia 26,27 , à deficiência de vitamina A 28 e à ingestão inadequada de energia e proteína 21 .…”
Section: Aspectos éTicosunclassified